Characterization of chitinases from the GH18 gene family in the myxomycete Physarum polycephalum - Renaud, Stéphanie; Dussutour, Audrey; Daboussi, Fayza; Pompon, Denis (Biochimica et biophysica acta. General subjects, 2023)
Physarum polycephalum is an unusual macroscopic myxomycete expressing a large range of glycosyl hydrolases. Among them, enzymes from the GH18 family can hydrolyze chitin, an important structural component of the cell walls in fungi and in the exoskeleton of insects and crustaceans. Low stringency sequence signature search in transcriptomes was used to identify GH18 sequences related to chitinases. Identified sequences were expressed in E. coli and corresponding structures modelled. Synthetic substrates and in some cases colloidal chitin were used to characterize activities. Catalytically functional hits were sorted and their predicted structures compared. All share the TIM barrel structure of the GH18 chitinase catalytic domain, optionally fused to binding motifs, such as CBM50, CBM18, and CBM14, involved in sugar recognition. Assessment of the enzymatic activities following deletion of the C-terminal CBM14 domain of the most active clone evidenced a significant contribution of this extension to the chitinase activity. A classification based on module organization, functional and structural criteria of characterized enzymes was proposed. Physarum polycephalum sequences encompassing a chitinase like GH18 signature share a modular structure involving a structurally conserved catalytic TIM barrels decorated or not by a chitin insertion domain and optionally surrounded by additional sugar binding domains. One of them plays a clear role in enhancing activities toward natural chitin. Myxomycete enzymes are currently poorly characterized and constitute a potential source for new catalysts. Among them glycosyl hydrolases have a strong potential for valorization of industrial waste as well as in therapeutic field. [Display omitted] •Slime mold P. polycephalum expresses a large number of GH18 glycoside hydrolases.•Sequences share decorated variants of the catalytic TIM barrel fold of chitinases.•Sugar binding motifs, such as CBM50, CBM18, and CBM14 are fused to the TIM barrel.•Three of the characterized enzymes efficiently hydrolyze colloidal chitin.•Functional roles of C-and N-terminal extensions were characterized and a classification proposed.